# Calculator search results

Formula
Solve the equation
Graph
$y = - 5 x + 4$
$y = 3 \left ( x + 4 \right )$
$x$-intercept
$\left ( \dfrac { 4 } { 5 } , 0 \right )$
$y$-intercept
$\left ( 0 , 4 \right )$
$x$-intercept
$\left ( - 4 , 0 \right )$
$y$-intercept
$\left ( 0 , 12 \right )$
$-5x+4 = 3 \left( x+4 \right)$
$x = - 1$
 Solve a solution to $x$
$- 5 x + 4 = \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \right )$
 Multiply each term in parentheses by $3$
$- 5 x + 4 = \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
$- 5 x + 4 = 3 x + \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
 Multiply $3$ and $4$
$- 5 x + 4 = 3 x + \color{#FF6800}{ 12 }$
$- 5 x + 4 = \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 12$
 Move the variable to the left-hand side and change the symbol 
$- 5 x + 4 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 12$
$- 5 x \color{#FF6800}{ + } \color{#FF6800}{ 4 } - 3 x = 12$
 Move the constant to the right side and change the sign 
$- 5 x - 3 x = 12 \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 12 - 4$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ x } = 12 - 4$
$- 8 x = \color{#FF6800}{ 12 } \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
 Subtract $4$ from $12$
$- 8 x = \color{#FF6800}{ 8 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 8 } \color{#FF6800}{ x } = \color{#FF6800}{ 8 }$
 Change the sign of both sides of the equation 
$8 x = - 8$
$\color{#FF6800}{ 8 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 8 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
 그래프 보기 
Graph
Solution search results